COMPARISON OF THERAPEUTICALLY INTERESTING BIOACTIVITY PROFILES OF WITHANIA SOMNIFERA EXTRACTS IN RODENT MODELS - Dey, Amitabha (IIT (BHU), Varanasi, 2018)
Ayurveda is the oldest known system of medicine still widely practiced in India and popularity of diverse therapeutic modalities mentioned in ancient Ayurvedic literature has continued to increase during recent decades. In Ayurveda, Rasayana herbs are always recommended for treating metabolic and neurologic conditions. Diabetes is a slowly and silently progressing metabolic disorder, which ultimately leads to structural and functional deteriorations of almost all bodily organs including those of circulating fluids and central and peripheral nervous systems. Diabesity has been associated with various co-morbidities including central nervous system (CNS) disorders such as depression, anxiety, cognitive dysfunctions, and neuropathic pain and inflammation. Treating mental health problems in diabetic patients however remains a challenging field in medical science. Many tonics or rejuvenators oftenly used in Ayurvedic system of medicine for prevention of psychiatric or neurologic comorbidities contain Ashwagandha concoctions as one of their major active ingredients and currently Ashwagandha is recommended by most of Ayurvedic practitioners for treating all such conditions. Ashwagandha (Withania somnifera) is a traditionally known rejuvenative herb of solanaceae family, and withanolides are quantitatively the major bioactive secondary metabolites of the plant identified and most currently commercialised Withania somnifera extracts or products are now often analytically characterised by their contents of total withanolides. Extensive efforts made during past few decades have identified not only broad spectrums of therapeutically interesting pharmacological properties of diverse types of Withania somnifera extracts obtained from different parts, but also of withanolides and other structurally unique bioactive constituents of such extracts. Amongst them the ones dealing with anti-stress, anticancer and anti-inflammatory activities of extracts
This Thesis Submitted by IIT (BHU ), Varanasi. PhD Scholar and Submitted by - Sushil Kumar Singh.
Keywords: COMPARISON; THERAPEUTICALLY; BIOACTIVITY PROFILES; SOMNIFERA